1997
DOI: 10.1111/j.1463-6409.1997.tb00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Cladistics and polychaetes

Abstract: A series of cladistic analyses assesses the status and membership of the taxon Polychaeta. The available literature, and a review by Fauchald & Rouse (1997), on the 80 accepted families of the Polychaeta are used to develop characters and data matrices. As well as the polychaete families, non‐polychaete taxa, such as the Echiura, Euarthropoda, Onychophora, Pogonophora (as Frenulata and Vestimentifera), Clitellata, Aeolosomatidae and Potamodrilidae, are included in the analyses. All trees are rooted using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
767
4
15

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 606 publications
(814 citation statements)
references
References 180 publications
(237 reference statements)
28
767
4
15
Order By: Relevance
“…The shape and position of these papillae suggests that these may correspond to sensory structures. Nevertheless, trichobranchids lack dorsal and ventral parapodial cirri (Fauchald and Rouse 1997). Therefore, only a detailed histological study might reveal the actual function of these papillae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape and position of these papillae suggests that these may correspond to sensory structures. Nevertheless, trichobranchids lack dorsal and ventral parapodial cirri (Fauchald and Rouse 1997). Therefore, only a detailed histological study might reveal the actual function of these papillae.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Terebellides usually has a single pair of segmental organs anterior to the gular membrane (the muscular septum between the two anterior segments) with excretory function. In addition a number of posterior pairs are also present for gamete release (Hessle 1917;Goodrich 1945and Bartholomaeus 1999in Rouse and Fauchald 1997. The latter occur in segments which often lack complete septa allowing interconnection of segmental coelomic cavities (Rouse and Pleijel 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the preparapodial and the postparapodial cirri of M. cirriferum can be homologized with ventral and dorsal cirri, respectively, of the polychaetes. Like M. cirriferum, many Myzostomida have 10 pairs of cirri (Prenant, 1959;Fauchald and Rouse 1997;Rouse and Fauchald, 1997;Eeckhaut et al, 1998), so that for each parapodium there is one ventral and one dorsal cirrus. In some species, however, the number of cirri is distinctly greater, and it remains for future studies to determine whether all of these are innervated by side branches of the parapodial nerves and how these nerves branch.…”
Section: Circumesophageal Connectives and Peripheral Nervous Systemmentioning
confidence: 99%
“…As Pietsch and Westheide (1987) pointed out, they have been considered to be either 1) a taxon outside the Annelida (Turbellaria, Trematoda, Tardigrada, parasitic Crustacea) (see Stummer-Traunfels, 1927;Jä gersten, 1940); 2) Annelida but not Polychaeta (Mecznikow, 1866;Brusca and Brusca, 1990); 3) a sister group of the "true" Polychaeta (Fedotov, 1929;Kato, 1952); or 4) a subtaxon of the Polychaeta (Beard, 1884;Wheeler, 1897). The serial arrangement of their chaetaebearing parapodia, protonephridia, and lateral organs suggests a segmented organization of the Myzostomida; for this reason, in most modern systems they are treated as Annelida and sometimes specified as Polychaeta (Barnes and Harrison, 1992;Westheide and Rieger, 1996;Fauchald and Rouse, 1997;Rouse and Fauchald, 1997). But other characters, chiefly the undivided coelom, the sequence of parapodia formation (3, 4, 2, 5ϩ1, Jägersten 1940;Eeckhaut et al, 1990), the variety of lateral organs (ranging in number from zero to 20 in the different species), and the assumed lack (Haszprunar, 1996) of segmentally arranged organs (serially arranged protonephridia have so far been reported only in Myzostoma cirriferum by Pietsch and Westheide [1987]) are used by other authors to interpret the Myzostomida as nonsegmented animals (Jägersten, 1940;Salvini-Plawen, 1980a,b;Haszprunar, 1996).…”
mentioning
confidence: 99%
“…It has long been admitted that the Polychaeta constitute the group closest to the Clitellata. However, it is still not clear whether they are to be considered as two separate clades or whether the clitellates have a sister group among the polychaetes (Rouse & Fauchald 1997;Westheide 1997). Molecular studies have suggested that clitellates are derived polychaetes, but most of these investigations included too few species for assessing the position of this taxon properly (among others McHugh 1997;Kojima 1998;Winnepenninckx et al 1998).…”
Section: Introductionmentioning
confidence: 99%